Citizen Science and Climate Change: Mapping the Range Expansions of Native and Exotic Plants with the Mobile App Leafsnap. (14th March 2018) - Kress, W John; Garcia-Robledo, Carlos; Soares, João V B; Jacobs, David; Wilson, Katharine; Lopez, Ida C; Belhumeur, Peter N
Abstract: The mobile iPhone app Leafsnap, designed for the automatic identification of 220 tree species from the northeastern United States, was released to the public in 2011. In the first 3 years of its use, the app was downloaded by more than 1, 500, 000 users from five continents and 181 countries who recorded over 3, 056, 684 leaf images. The high levels of accuracy of Leafsnap identifications, as were confirmed by expert botanists, were used to map the geographic distribution of native and exotic species at a scale previously unachievable without this technology and without the aid of citizen scientists. Species demonstrated northerly migrations, southerly migrations, or little change from their estimated distributions in the 1950s. These results suggest that this tool carried on the phones of millions may potentially collect invaluable data that can be used to monitor the effects of climate change and exotic species on tree distributions at broad geographic scales.